Decompression via unilateral biportal endoscopy for severe degenerative lumbar spinal stenosis: A comparative study with decompression via open discectomy - Tan, Bing; Yang, Qi-Yuan; Fan, Bin; Xiong, Chuang (Frontiers in Neurology, 2023)
Background:Previous studies have shown that the Unilateral Biportal Endoscopy is an effective and safety surgery for sufficient decompression of degenerative lumbar spinal stenosis.However, data are lacking in terms of its benefits when compared with conventional open lumbar discectomy(OLD), especially in patients with severe degenerative lumbar spinal stenosis(DLSS). Aim:To compare the clinical outcomes of two types decompressive surgery: unilateral biportal endoscopy-unilateral laminectomy bilateral decompression (UBE -ULBD) and conventional open lumbar discectomy(OLD) in severe degenerative lumbar spinal stenosis (DLSS). Results The baseline demographic data of the 2 groups were comparable, including VAS, ODI and ZCQ scores, the cross-sectional area of the thecal sac and paraspinal muscles and creatine kinase levels. The dural sac CSA significantly increased postoperatively in both groups, which confirmed they benefited from comparable decompressive effects. The operative duration in the OLD group was less than the UBE-ULBD group (43.9±5.6minutes vs. 74.2±9.3minutes, p<0.05). The OLD group was associated with more estimated blood loss than the UBE-ULBD group (111.2±25.0ml vs. 41.5±22.2ml, P<0.05). The length of hospital stay (HS) was significantly longer in the OLD group than in the UBE-ULBD group (6.8±1.6 vs. 4.0±1.4 days, P<0.05). The VAS, ODI, and ZCQ scores improved in both groups after the operation. Serum creatine kinase values in the UBE-ULBD group were significantly lower than in the OLD group at 1 day after surgery (108.1±11.9 vs. 347.0±19.5U/L, P<0.05). The degree of paraspinal muscle atrophy in the UBE-ULBD group was significantly lower than in the OLD group at 1 year (4.50±0.60 vs. 11.42±0.87, P<0.05). Conclusions UBE-ULBD and conventional OLD demonstrate comparable short-term clinical outcomes in treating severe DLSS. However, UBE-ULBD surgery was associated with a shorter hospital stay, less EBL and paravertebral muscle injury than OLD surgery.